Helping at-risk students : a group counseling approach for grades 6-9 - Waterman, Jill; Walker, Elizabeth (New York : Guilford Press, 2001)
This book provides a comprehensive, empirically supported group counselling program for students in grades 6-9 at risk for academic, behavioral, and emotional difficulties. Designed for implementation in the span of a school semester, the curriculum has been shown to foster competence in areas crucial to successful development. The SPARK curriculum has 7 modules, each with several sessions. Each of the modules addresses issues salient for at-risk youth (Trust Building and Communication Skills, Anger Management and Problem-Solving Skills, Ethnic Identity and Anti-Prejudice, Educational Aspirations, Peer Pressure and Gangs, Exposure to Violence and Posttraumatic Stress Reactions, and Family Relationships). Activities and discussions that facilitate exploration of these issues are described. The curriculum is called SPARK because it is intended to spark greater student achievement, social-emotional growth, and nonviolent responding. It combines a group process model and a psychoeducational model.
Appendix D. Curriculum materials and handouts in Spanish